The Decipherment of the Minoan Linear A and Pictographic Scripts - Davis, Simon (1967)
The Cretan Scripts - The Syllabic Systems - Preliminary Indications as to the Language of Linear A – The Writing Conventions of Linear A – The Hagia Triada Tablets – The Arkalochori Bronze Axe and the Phaistos Disk – Other Pictographic Inscriptions – The Acrophonic Principle – Survivals: the Eteocretan Inscriptions – The Eteocypriote Inscriptions. Appendices: Motifs of Select Early Minoan Seals – The Group of Seals, Tholos II, Rutsi – Some Significant Seals – Sealings from the House of the Tiles, Lerna – Seals from Troy – Seals from Alaja Hüyük – The Decipherment of Cypro-Minoan: A Tablet from Enkomi – Select List of Hittite (Cuneiform) Words Quoted; R16/£8/$23.20; cf. 29:415 und 557.